BS EN 61587-1 Ed.5.0. Mechanical structures for electrical and electronic equipment. Tests for IEC 60917 and IEC 60297 series. Part 1. Environmental requirements, test set-up and safety aspects (5th June 2020) - British Standards Institution,
No abstract available